2023
DOI: 10.1371/journal.pone.0284289
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced corticospinal excitability in the tibialis anterior during static stretching of the soleus in young healthy individuals

Abstract: Corticospinal excitability is known to be affected by afferent inflow arising from the proprioceptors during active or passive muscle movements. Also during static stretching (SS) afferent activity is enhanced, but its effect on corticospinal excitability received limited attention and has only been investigated as a single average value spread over the entire stretching period. Using transcranial magnetic stimulation (TMS) the present study was conducted to explore the time course of corticospinal excitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Jumping and sprinting for maximal performance would involve high motor unit recruitment especially of the type II fast twitch motor units, which would be fired at high firing frequencies, with some degree of synchronization, while coordinating the activation of agonists, antagonists, synergists and stabilizer muscles ( Behm, 1995 ). Although, Budini and Christova. (2023) proposed motor evoked potentials to be greater while stretching, which might attributable to muscle spindle induced corticomotor facilitation, Magnusson et al (1996) reported no changes in hamstrings EMG activity during a 3 week stretch training protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Jumping and sprinting for maximal performance would involve high motor unit recruitment especially of the type II fast twitch motor units, which would be fired at high firing frequencies, with some degree of synchronization, while coordinating the activation of agonists, antagonists, synergists and stabilizer muscles ( Behm, 1995 ). Although, Budini and Christova. (2023) proposed motor evoked potentials to be greater while stretching, which might attributable to muscle spindle induced corticomotor facilitation, Magnusson et al (1996) reported no changes in hamstrings EMG activity during a 3 week stretch training protocol.…”
Section: Discussionmentioning
confidence: 99%